Optimalisasi Internet Of Things Sebagai Upaya Mitigasi Bencana Pendidikan Anak Usia Dini Permata Hati, Masangan Kulon, Sidoarjo - Aziz, Muhammad Hilmy (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Disaster mitigation becomes crucial when faced with the fact that the population in a country is threatened with safety by settlements located in disaster-prone areas. The Internet of Things is the main supporting instrument in disaster mitigation efforts. It is inevitable that the use of the internet has now become a part of human life, especially in the context of learning in early childhood. This research focuses on the extent to which the Internet of Things can be used as a medium to optimize disaster mitigation efforts, in this case, as an application of learning in Early Childhood Education (PAUD). The goal is to review that in following the times, there is a new medium to provide internet-based education in terms of disaster mitigation, and it has become an interesting thing to apply. The method used is qualitative, which can portray in detail the location of the problem at hand. At least in this research, the results show that schools and technology are a whole unit to be able to create a synergy between educators and students. This is very useful for instilling disaster mitigation literacy as early as possible to be used as an initial provision in knowing the concept of a disaster, especially in disaster-prone areas. By optimizing supporting instruments on the internet, students can learn, understand, and apply the attitudes that must be taken when in a certain emergency condition.